A delayed and unsynchronized ovary development as revealed by transcriptome of brain and pituitary of Coilia nasus - Yu, Ziyan; Gao, Zongshuai; Zeng, Yun; Li, Mingyou; Xu, Gangchun; Ren, Mingchun; Zhu, Yunxia; Liu, Dong (Frontiers in Molecular Biosciences, 2024)
Coilia nasus is an anadromous fish that has been successfully domesticated in the last decade due to its high economic value. The fish exhibits a delayed ovary development during the reproductive season, despite breeding and selection for 5-6 offspring. The molecular mechanism of the delayed ovary development is still unknown, so the obstacles have not been removed in the large-scale breeding program. This study aims to investigate the key genes regulating ovarian development by comparing the transcriptomes of ovarian-stage IV and stage II brain/pituitary of C. nasus. Ovarian stages were validated by histological sections. A total of 75,097,641 and 66,735,592 high-quality reads were obtained from brain and pituitary transcriptomes, respectively, and alternatively spliced transcripts associated with gonadal development were detected. Compared to ovarian Ⅱ-brain, 515 删除的内容:differentially expressed genes (DEGs) were upregulated and 535 DEGs were downregulated in ovarian Ⅳ-brain, whereas 470 DEGs were upregulated and 483 DEGs were downregulated in ovarian Ⅳ-pituitary compared to ovarian Ⅱ-pituitary. DEGs involved in hormone synthesis and secretion and in the GnRH signaling pathway were screened. Weighted gene co-expression network analysis identified gene co-expression modules that were positively correlated with ovarian phenotypic traits. The hub genes Smad4 and TRPC4 in the modules were co-expressed with DEGs including Kiss1 receptor and JUNB, suggesting that ovarian development is controlled by a hypothalamic-pituitary-gonadal axis. Our results have provided new insights that advance our understanding of the molecular mechanism of C. nasus reproductive functions and will be useful for future breeding.